Ankle Evertor Strength of Healthy Subjects in Different Ankle and Toe Positions - Ahn, Sun-hee; Kim, Hyun-a; Kim, Jun-hee; Kwak, Kyung-tae; Kwon, Oh-yun (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2019)
Background: Ankle evertor muscles are important for preventing lateral ankle sprain. Since, the evertor muscles cross the ankle and toe joints, the position at which the ankle evertor muscle strength is measured is important. However, no studies have previously investigated the effect of ankle and toe positions on the strength of the ankle evertor muscle. Objects: This study is aimed to determine the effect of various ankle and toe joint positions on the strength of the ankle evertor muscles in healthy subjects. Methods: Eighteen healthy subjects participated in this study. Isometric ankle evertor strength of the dominant leg was determined in each subject in different ankle and toe positions (dorsiflexion (DF) with toe extension (TE), DF with toe flexion (TF), plantar flexion (PF) with TE, and PF with TF). A 2 by 2 repeated analysis of variance (ANOVA) was used to determine the difference in the evertor strength between the ankle positions (PF and DF) and toe positions (TE and TF). Results: The results indicate that there was no significant ankle position by toe position interaction effect (p=.83). However, the ankle evertor strength was significantly increased in the ankle DF position than in the PF position (p<.01), and the ankle evertor strength during eversion with TE was significantly higher than eversion with TF (p<.01). Conclusion: The findings of this study suggest that clinicians should consider the ankle and toe positions when measuring the muscle strength and during performance of selective muscle strengthening exercises of the ankle evertor muscles. KCI Citation Count: 0